Ultrasound, Echocardiography, MRI, and Genetic Analysis of a Fetus with Congenital Diaphragmatic Hernia and Partial 11q Trisomy - Yolanda Fernández-Perea; Lutgardo García-Díaz; Javier Sánchez; Guillermo Antiñolo; Salud Borrego (Case Reports in Obstetrics and Gynecology)
Congenital diaphragmatic hernia (CDH) is a serious birth defect with a significant mortality and morbidity. The current and constant progress in ultrasound techniques has led to the improvement of the prenatal diagnosis of this malformation. CDH is a developmental defect whose etiology is heterogeneous and takes place when the pleuroperitoneal folds and septum transversum fail to converge and fuse. Survival depends on the extent of pulmonary hypoplasia and the disease may be potentially worsened by the presence of added congenital defects. 40% of CDH cases are associated with at least one additional anomaly. The ultrasound diagnosis is established with essential signs: loss of uniform echogenicity of lungs and marked mediastinal shift. We report the case of a fetus with isolated CDH diagnosed at 21 weeks of gestation by ultrasound and confirmed by RMI, whose genetic analysis of amniotic fluid cells identified a de novo partial trisomy of the long arm of chromosome 11. Different genetic causes have been associated with CDH. Moreover, it is expectable that the use of new techniques for prenatal diagnosis will reveal novel CNVs associated with CDH and will help us to estimate the recurrence risk for this defect as well as for other associated anomalies.